Determinants of Independent Director Compensation: An Exploratory Study in a Socialist Capitalist Economy - Adithipyangkul, Pattarin; Leung, T.Y. (European Accounting Association, 2012)
This paper examines the determinants of Chinese independent director compensation by considering (i) director characteristics such as age, gender, education level, professional expertise, and experience, (ii) board characteristics such as board size and board independence, and (iii) firm characteristics such as ownership structure, firm age", firm size, and firm performance. The research finds that independent director compensation is determined by director's human capital, as measured by professional expertise, work experience, and education level. We also find that the firm characteristics and director's attributes interact to determine independent director pay.